SUBSTITUTION OF FISHMEAL WITH SOYBEAN MEAL IN HUMPBACK GROUPER, Cromileptes altivelis JUVENILE DIETS SUPPLEMENTED WITH PHYTASE - Rachmansyah Rachmansyah; Usman Usman; Makmur Makmur; Taufik Ahmad (Research Center for Fisheries, 2005)
Feeding experiments were conducted to evaluate the effects of replacing fishmeal with soybean meal in di6t on grolvth of humpback grouper.